2022
DOI: 10.4322/bds.2022.e3406
|View full text |Cite
|
Sign up to set email alerts
|

Low level laser therapy versus benzydamin in prevention and treatment of oral mucositis induced by anticancer treatments (clinical and biochemical study)

Abstract: Low level laser therapy versus benzydamin in prevention and treatment of oral mucositis induced by anticancer treatments (clinical and biochemical study)Terapia a laser de baixa intensidade versus benzidamina na prevenção e tratamento da mucosite oral induzida por terapia oncológica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Ionization irradiation causes local infection, suture dehiscence, and mucositis [12,17,18]. In the present study, alopecia, ulceration and radiodermatitis were observed.…”
Section: Discussionsupporting
confidence: 57%
“…Ionization irradiation causes local infection, suture dehiscence, and mucositis [12,17,18]. In the present study, alopecia, ulceration and radiodermatitis were observed.…”
Section: Discussionsupporting
confidence: 57%
“…Table 3 presents detailed information on the descriptive characteristics of the included studies, such as authors, year of publication, type of study, sample size, OM assessment scale and associated pain, degree of mucositis, oral hygiene habits; and laser characteristics, such as energy density, wavelength and power. Among the articles included, there are seven clinical trials [4,[11][12][13][14][15][16] and two pilot studies [17,18].…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
“…Sample sizes in the studies ranged from 16 to 85 patients, aged between 10 months and 18 years. To assess the degree of OM, seven studies [11][12][13][14][16][17][18] used the World Health Organization (WHO) scale, while only two studies [4,15] used the toxicity criteria recommended by the National Cancer Institute (NCI).…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations